PARA UMA POÉTICA DA VITALIDADE: religião e antropologia na escritura machadiana (Uma leitura de Memórias póstumas de Brás Cubas, de Machado de Assis) - Conceição, Douglas Rodrigues da (2007)
The literature of Machado de Assis is being revisited in this thesis, due to our belief that the theme of religion and its implications to the human being conceived by Machado required an investigative task that was awaiting to be accomplished. In order to centralize the main issue of the present thesis in the discussion field that is constituted by the debates between literature and religion, we structured, in the first part of our text, a path that enabled us to conclude that the approximation of both literature and religion is truly effective. Supported by the extensive discussion on the religious and theological images contained in the literary texts, as well as the several methodological constructions that aim at appeasing a more profitable approach between religion and literature, we proceeded to an interpretation of Machado s literature in which the religious manifestation, on the viewpoint of the anthropology of his works, could be truly detached. The starting point of our interpretative basis was Paul Ricoeur s hermeneutics, more specifically his concepts on the metaphor. Our reflection on the religious expression of the machadian anthropology was, initially, centered on the concept of vitality, coined by Jürgen Moltmann. The religious expression of the machadian anthropology manifested in the novel Memórias póstumas de Brás Cubas (1881) is represented under the perspective of an unconditionality from which Brás Cubas life is comprised. This characteristic of the machadian anthropology encouraged us to create a new concept that could express the originality of Machado s thought accordingly. Therefore, we propose homo vitalis as the key concept to define the human being represented by Machado de Assis in his literary space.(AU)